2018
DOI: 10.1186/s40249-018-0410-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of five annual rounds of mass drug administration with ivermectin on onchocerciasis in Sierra Leone

Abstract: BackgroundOnchocerciasis is endemic in 12 of the 14 health districts of Sierra Leone. Good treatment coverage of community-directed treatment with ivermectin was achieved between 2005 and 2009 after the 11-year civil conflict. Sentinel site surveys were conducted in 2010 to evaluate the impact of five annual rounds of ivermectin distribution.MethodsIn total, 39 sentinel villages from hyper- and meso-endemic areas across the 12 endemic districts were surveyed using skin snips in 2010. Results were analyzed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Similar studies aimed to determine onchocerciasis MF prevalence and CMFL have been reported in Sierra Leone and Cameroon after repeated annual treatment with ivermectin [ 22 , 23 ]. Our findings are similar to those recently reported in Sierra Leone where skin MF prevalence were still between 10 and 30% after implementation of 5 continuous MDA rounds with ivermectin [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar studies aimed to determine onchocerciasis MF prevalence and CMFL have been reported in Sierra Leone and Cameroon after repeated annual treatment with ivermectin [ 22 , 23 ]. Our findings are similar to those recently reported in Sierra Leone where skin MF prevalence were still between 10 and 30% after implementation of 5 continuous MDA rounds with ivermectin [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…This significant reduction may have been partly due to the use of ivermectin for onchocerciasis control, as reported in some other countries [ 28 , 29 ]. In Sierra Leone, ivermectin was used pre-conflict in limited space in the country [ 30 ], but large scale use through CDTI did not start until 1995 as the Special Intervention Zone of the African Programme of Onchocerciasis Control, in meso- and hyper-endemic villages [ 13 ]. However, due to the civil conflict between 1991–2002, CDTI did not achieve satisfactory treatment coverage until 2005 and was expanded to accommodate district-wide LF MDA by adding albendazole in 2007–2008 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Sierra Leone, ivermectin was used pre-conflict in limited space in the country [ 30 ], but large scale use through CDTI did not start until 1995 as the Special Intervention Zone of the African Programme of Onchocerciasis Control, in meso- and hyper-endemic villages [ 13 ]. However, due to the civil conflict between 1991–2002, CDTI did not achieve satisfactory treatment coverage until 2005 and was expanded to accommodate district-wide LF MDA by adding albendazole in 2007–2008 [ 13 ]. Therefore, the prior ivermectin use in the 12 dsitricts may have contributed to the reduction of LF prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sierra Leone, civil conflict also resulted in limited onchocerciasis control activities from 1991–2002, but after the war, good CDTi was achieved between 2005 and 2009. In 2010, after 5 rounds of ivermectin, 10 out of 12 endemic districts had a >50% reduction in mf prevalence and 11 of 12 districts had ≥50% reduction in mean mf density among the positives, suggesting that Sierra Leone will now be on course to achieve elimination by the year 2025 [ 90 ].…”
Section: Update On Onchocerciasis Control Programs and Eliminationmentioning
confidence: 99%